Detection and Characterization of Paslahepevirus balayani (Hepatitis E Virus) in Dairy Products from Hebei Province, China - Xinyue Hu; Jinfeng Wang; Yinuo Wang; Wanzhe Yuan; Jianchang Wang; Xiangdong Xu (Pathogens)
Paslahepevirus balayani (hepatitis E virus), a zoonotic pathogen transmitted primarily via the fecal–oral route, has undergone shifting transmission dynamics in China, with foodborne and zoonotic routes becoming increasingly significant. To assess the potential risk of HEV transmission through dairy products, this study investigated HEV RNA presence in raw milk from cows, sheep, and goats in Hebei Province, China. From March 2024 to April 2025, we collected 102 cow milk, 18 sheep milk, and 59 goat milk samples, analyzing them using RT-qPCR, with positive samples confirmed by RT-Nested PCR and partial ORF2 sequencing. While no HEV RNA was detected in cow milk, 3/18 (16.67%) sheep milk and 1/59 (1.69%) goat milk samples tested positive. Phylogenetic analysis of two sheep-derived and one goat-derived HEV isolate showed 99.43–100% nucleotide identity to local swine HEV strains (HEV/HB-SJZ158/CHN/2021 and HEV/HB-CD28/CHN/2021), all clustering within genotype 4d, the dominant subtype in the region. This study provided the first evidence of HEV RNA in sheep and goat milk in Hebei Province, suggesting possible cross-species transmission from pigs to ruminants. These findings highlighted the need for further research on HEV transmission risks through dairy products and emphasize the importance of monitoring zoonotic HEV strains in food safety assessments.